2000
DOI: 10.1016/s0022-5347(05)67014-0
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Live Donor Nephrectomy: The University of Maryland 3-Year Experience

Abstract: Laparoscopic donor nephrectomy appears to be safe and decreases morbidity in the renal donor. Allograft function is comparable to that in open nephrectomy series. The availability of laparoscopic harvesting may be increasing the living donor volunteer pool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
64
2
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(73 citation statements)
references
References 3 publications
5
64
2
2
Order By: Relevance
“…Other studies of laparoscopic graft survival have shown results (91-95%) similar to those of our study [14,28,30]. The number of rejection episodes also did not differ significantly between the HALDN (8/118, 6.8%) and the ODN (7/123, 5.1%) groups (p=0.435), nor did other complications, such as ureteral complications (p=0.392).…”
Section: Discussionsupporting
confidence: 87%
“…Other studies of laparoscopic graft survival have shown results (91-95%) similar to those of our study [14,28,30]. The number of rejection episodes also did not differ significantly between the HALDN (8/118, 6.8%) and the ODN (7/123, 5.1%) groups (p=0.435), nor did other complications, such as ureteral complications (p=0.392).…”
Section: Discussionsupporting
confidence: 87%
“…Tributaries of the left renal vein, and especially the posterior lumbar branches, are of potential surgical importance if they are noted to be enlarged. The left kidney is preferred for laparoscopic donor nephrectomy due to the longer renal venous pedicle; however, a right nephrectomy may be performed if complex vascular anatomy precludes resection of the donor's left kidney (8). …”
Section: Normal Renal Vascular Anatomymentioning
confidence: 99%
“…Jacobs et al reported the initial 3-year experience at the University of Maryland. 2 Among 320 consecutive laparoscopic live donors, the mean ischaemia time was 2.5 min, and 98% of grafts showed immediate graft function. With increasing experience, the ureteric stricture rate, which was high in the initial reports, has decreased significantly by paying attention to preserving the ureteric blood supply.…”
Section: Discussionmentioning
confidence: 99%
“…To reduce the morbidity of donors, who are healthy individuals, laparoscopic donor nephrectomy (LDN) is increasingly accepted as a safe and preferred surgical option. [1][2][3][4] However, the overall number of renal transplants in Hong Kong remains low. From 2006 to 2009, 262 deceased donor renal transplants were carried out; in comparison, 30 live donor transplants were carried out during that period.…”
mentioning
confidence: 99%